KAJIAN PENDAPATAN NELAYAN KEPITING BAKAU (Scylla serrata) DI KECAMATAN SAMATIGA KABUPATEN ACEH BARAT - Teuku Amarullah; Syarifah Zuraidah; Gunawan Gunawan (JURNAL PERIKANAN TROPIS, 2018)
The research has been conducted on "The Study of Fishermen’s Income of Mangrove Crabs (Scylla serrata) in the Samatiga District of West Aceh Regency". This research purpose is to analyze the income of fishermen’s mangrove crabs and to determine the feasibility of mangrove crab business. In this research, the sampling method by using census, amount of sampling as much as 11 fishermen. To know the level ofthe income in fishermen mangrove crabs in the Samatiga District by using quantitative and qualitative analysis. The average of amount of mangrove crabs production produced by each fisherman in one year is about 689,23 kg with the selling price of Rp. 50.000/kg. The average amount of gross income earned by each fisherman is Rp. 34,461,818 /year and total costas much as Rp 10,112,455/year, then each fisherman earns a profit as much as Rp. 24.349.362 /year, if calculated in per month as much as Rp. 2,029.113 / month. And per day as much as Rp. 78.042 / day. R / C ratio value that is obtained is 3,40 which means such business is feasible or profitable. Keywords: Study, Fishermen's Income, Mangrove Crabs